Analysis of the Implementation of Green Financing at PT Bank Syariah Indonesia Tbk in Supporting the National Net Zero Emission Target - Muhammad Aldi Pratama; Tuti Anggraini; Wahyu Syarvina (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Indonesia's commitment to achieving Net Zero Emission (NZE) by 2060 requires the active involvement of all sectors, including the financial sector. Islamic banking has a strategic role through the implementation of green financing that aligns with sustainability principles and the maqashid of Sharia. This study aims to analyze the implementation of green financing in Bank Syariah Indonesia in supporting the national net zero emission target. The research method used is qualitative descriptive with a case study approach. The data obtained in this study consisted of documentation studies of annual reports, sustainability reports, sustainable financing policies, and official publications available on the BSI website for the period 2023-2025. The results of the study indicate that Bank Syariah Indonesia has implemented green financing through the provision of sustainable financing in the renewable energy sector, eco-efficient products, sustainable land management, as well as financing for environmentally-oriented micro, small, and medium enterprises. This study concludes that the implementation of green financing at Bank Syariah Indonesia plays an important role in supporting national net-zero emission targets, although there are still various challenges in its implementation.